Communication in the medical team (methodical recommendations) - Abdrjahimova Ціра; Mukharovska Інна; Kleban Катерина; Sapon Дарія; Kalachov Олексій (Psychosomatic Medicine and General Practice, 2020)
The quality of care depends not only on medical skills but also on the communicative competencies of healthcare professionals. The article deals with the main psychological aspects of the professional activity of doctors in the medical team, namely, the role of the team, leadership, psychological profile, corporate culture, typical situations of interaction (counseling of patients of another specialist, clinical bypass), professional deformation, factors of formation and manifestations burnout, its prevention. Medico-psychological interventions aimed at enhancing the psychological competencies of health care professionals will improve the quality of care for patients and the psychological health of professionals.